Paradigm Shift at Medika Utama Hospital: From A Doctor-Centric Approach to Patient-Centered Digital Services - Sri Wahyuni; Mahdiansyah Mahdiansyah; Ismaul Khusna; Noorhikmah Ramadani; Muhammad Fajar Rifana; H. Muhammad Zazuli (PT. Hanken Sukses Jaya, 2025)
Hospital digital transformation has become a strategic agenda to enhance service efficiency, quality of care, and organizational competitiveness. However, the success of digital transformation is determined not merely by technology adoption, but also by organizational readiness, culture, leadership, and effective change management. This study aims to analyze the paradigm shift at Medika Utama Hospital from a doctor-centric approach to patient-centered digital services, while identifying the factors underlying the initial failure of digitalization initiatives. The research employs a qualitative approach using a case study design, based on secondary data analysis and an extensive literature review. The findings reveal that the digital transformation process remains largely technocratic, triggering organizational resistance, structural inertia, and weak transformational leadership. These results underscore that hospital digital transformation requires an organizational development approach, cultural change, and continuous learning to effectively realize patient-centered services.